Effect of laser power and heat treatment on microstructures and tensile properties of LPBF fabricated Hastelloy X superalloy - Jie Bai; Rui Ma; Yunlong Zhang; Liang Cheng; Yajun Wang; Weitian Zhou (Materials Research Express, 2023)
Laser powder bed fusion (LPBF) technic is suitable for manufacturing metal parts with complex shapes and internal channels. The energy input and post heat treatment have great influence on the formability, microstructure and properties of the metallic materials. In this work, Hastelloy X superalloy is fabricated by LPBF with a variation of laser power, and then post-treated by hot isostatic pressing and solution treatment. Influences of laser power and heat treatment on microstructure features of as-built sample are evaluated. The correlation among laser power, microstructure features and tensile properties of heat-treated samples are revealed. The results reveal that average grain size, aspect ratio, texture intensity increases while the proportion of high-angle grain boundaries decreases with the increase of laser power. Precipitates of Cr-rich carbides along grain boundary are observed after post heat treatment. Post-treatment promotes the twinned recrystallization, grain coarsening and texture degradation. Yield strength increases while tensile strength decreases with the increase in laser power. The higher vertical yield strength of sample with laser power of 320 W could be attributed to its larger aspect ratio and more twin boundaries. 280 W is the preferred laser power to obtain the best overall tensile properties. This study is helpful for the exploration of optimal LPBF process and post heat treatment, by which Ni-based superalloys with a good balance between strength and ductility can be produced.